A BASIC PHASE SHIFT FULL BRIDGE DC-DC CONVERTER DESIGN AND SIMULATION - Kucuk, Seyma; Akboy, Erdem (IEEE, 2022)
Full Bridge (FB) converters are used in the industrial applications such as switch mode power supplies, high voltage power supplies, battery chargers and welding machines etc. FB isolated DC-DC converters provide a safe charging process by providing galvanic isolation between the battery and the mains. Since the efficiency of the battery charger largely depends on the efficiency of the DC-DC converters, DC-DC converters are very important for battery chargers. However, at FB converters, the parasitic oscillations between the parasitic capacitors of the switches and the leakage inductance of the transformer can reach unacceptable levels for switching losses. Therefore, phase-shift method can be used to provide Soft Switching (SS). At this method, the overlapping of the current and voltages of the switches are reduced and so switching losses are decreased. Moreover current and voltage stresses of power components and Electro Magnetic Interference (EMI) are decreased. It is suitable and preferred for battery chargers in EV technology. In this study, a phase shift FB converter is presented. The design parameters and simulation results are given for input voltage of 385V DC, switching frequency of 50 kHz, and output of 250 W / 48 V.
Keywords: DC-DC converter; full bridge; soft switching; zero voltage transition; zero voltage switching; phase shifting PWM; PS-PWM; ZVS; ZVT; FB DC/DC CONVERTER; ZERO-VOLTAGE; HIGH-POWER; PWM CONVERTER; Energy & Fuels; Engineering